Factors of the epidemiological triad that influence the persistence of human papilloma virus infection in women with systemic lupus erythematosus (2018)
We studied the epidemiologic triad-related factors influencing human papilloma virus (HPV) persistence in Mexican women with systemic lupus erythematosus (SLE). Patients aged ?18 years with SLE (American College of Rheumatology criteria), with and without HPV persistence, were selected. Groups were analyzed by (1) host: clinical disease characteristics; (2) agent: (I) infectious (prevalence, incidence, HPV genotype and co-infections (?2 HPV genotypes or mycoplasmas)), (II) chemical (contraceptives and immunosuppressive drugs) and (III) physical (vitamin D deficiency) and (3) environment. A total of 121 SLE patients were selected over a two-year period. (1) Host: mean age 45.8 years and disease duration 12.7 years. (2) Agent: (I) infectious. HPV infection prevalence in the second sample was 26.4%, high-risk HPV genotypes 21.5% and co-infections 7.4%. HPV infection incidence was 13.2%, persistence 13.2% and clearance 15.7%. (II) Chemical: use of oral hormonal contraceptives 5% and immunosuppressive treatment 97.5%. (III) Physical: Vitamin D levels were similar in both groups. (3) Environment: (I) natural. A total of 60.6% of patients were residents of Puebla City. (II) Social: The mean education level was 10.9. Poverty levels were: III degree 52.4%, IV degree 28% and II degree 17%. (III) Cultural behavioral: Onset of sexual life was 20.5 years, 10% had ?3 sexual partners and 51.2% were postmenopausal. In conclusion, no factor of the epidemiologic triad was associated with HPV infection prevalence. © The Author(s) 2018.